Transformation for better living environment in urban region: application of the principle of transboundary liability and the montreal protocol experiences. - Muhammad Rizal Razman,; Abdul Samad Hadi,; Jamaluddin Md Jahi,; Shaharudin, (Universiti Kebangsaan Malaysia, 2011)
The international environmental law principle on transboundary liability plays an important role in transforming better living environment in urban region. The use of the international environmental law principle on transboundary liability in urban region for better living environment is largely in response to the inevitability of every individual to protect his/ her rights on living environment in urban region from being polluted. This article examines the use of the international environmental law principle on transboundary liability in transforming better living environment in urban region by identifying actions and cases which deal with human habitat and environmental protection in urban region. This article also identifies the relation between the international environmental law principle on transboundary liability and Rio Declaration as a means to transform better living environment in urban region. The opportunity to enhance the growth of this principle of transboundary liability in protecting human habitat and environment in urban region, through state practices, following the two-transboundary environmental disasters “Sandoz Spill” and “Chernobyl Explosion,” were lost due to the decision by the injured states not to take international legal actions for causing environmental pollution to their urban regions, even though the injured states have their right to do so. The support made by the statesaround the globe on the International Law Commission’s Draft Articles on the Non-Navigational Uses of International Watercourses Law, 1994 and the Rio Declaration, 1992 clearly reflected the acceptance and the growth of this principle of transboundary liability in protecting human habitat and environment especially in urban region. Finally, the preliminary findings indicate that the influence of interest approach in the international environmental governance is an important aspect to promote and persuade states around the globe to participate in the Montreal Protocol for the purpose to protect global environment by taking into consideration the principle of transboundary liability in order to control world emissions of pollution especially in urban region. These actions are to ensure the transformation for better living environment in urban region